Religiosity, Self-Esteem, and Parental Involvement in Child Education: Keagamaan, Harga Diri, dan Peran Orang Tua dalam Pendidikan Anak - Rachman, Risca Setya; Mariyati, Lely Ika (Indonesian Journal of Islamic Studies, 2025)
General background: Parental involvement is a crucial factor in supporting children’s learning development, yet many parents remain insufficiently engaged in their child’s education. Specific background: Religiosity has been associated with parenting practices, but its role in shaping parental involvement remains inconclusive, particularly when psychological constructs such as self-esteem are considered. Knowledge gap: Prior studies often examined religiosity and parental involvement separately, with limited attention to self-esteem as a mediating variable. Aims: This study investigates the relationship between religiosity and parental involvement, with self-esteem serving as a mediator. Results: A survey of 248 parents from SDN X in Krian District, Sidoarjo, analyzed using a mediation path model, revealed that religiosity had a significant direct relationship with parental involvement (z = 3.625, p < 0.001). Additionally, self-esteem significantly mediated this relationship (z = 2.324, p = 0.020). Novelty: The study demonstrates the psychological pathway by which religiosity translates into active parental participation through self-esteem, adding a new dimension to existing parenting models. Implications: Findings suggest that strengthening both religiosity and parental self-esteem may foster more consistent involvement in children’s education and care. Highlights: Religiosity directly predicts parental involvement. Self-esteem significantly mediates this relationship. Study introduces a psychological pathway in parenting research. Keywords: Parental Involvement, Religiosity, Self-Esteem, Mediation, Parenting